A rule-based semantic matching of base object models. (22nd September 2009) - Moradi, Farshad; Ayani, Rassul; Mokarizadeh, Shahab; Tan, Gary
Creating simulation models via composition of predefined and reusable components is an efficient way of reducing costs and time associated with the simulation model development. However, to successfully compose models one has to solve the issues of syntactic and semantic composability of components. The Base Object Model (BOM) standard is an attempt to ease reusability and composition of simulation models. However, the BOM does not contain sufficient information for defining necessary concepts and terms to avoid ambiguity, and neither does it have any method for dynamic aspects matching conceptual models (i.e., their state-machines). In this paper, we present our approach for enhancement of the semantic contents of BOMs and propose a three-layer model for syntactic and semantic matching of BOMs. The enhancement includes ontologies for entities, events and interactions in each component. We also present an OWL-S description for each component, including the state-machines. To test our approach, we specify some simulation scenarios and implement BOMs as building blocks for development of those scenarios, one of which is presented in this paper. We also define composability degree, which quantifies closeness of the composed model to a given model specification. Our results show that the three-layer model is promising and can improve and simplify the composition of BOM-based components.